The Use Of Ac/Dc Regenerative Drives On Continuous Miners And Shuttlecars - R. A. Hill (Society for Mining, Metallurgy & Exploration, 1986)
A brief explanation of the theoretical functioning of a regenerative system followed by its application to firstly, shuttlecars and then continuous miners and its effect on performance thereof with regard to handling, production and safety.